Tsc1 (hamartin) confers neuroprotection against ischemia by inducing autophagy - Papadakis, Michalis; Hadley, Gina; Xilouri, Maria; Hoyte, Lisa C.; Nagel, Simon; McMenamin, M. Mary; Tsaknakis, Grigorios; Watt, Suzanne M.; Drakesmith, Cynthia Wright; Chen, Ruoli; Wood, Matthew J. A.; Zhao, Zonghang; et al. (Nature medicine, 2013)
Neurons within the CA3 region of the hippocampus are relatively resistant to cell death after ischemia. Alastair M. Buchan and his colleagues demonstrate that the product of the TSC1 gene, hamartin, is upregulated in CA3 neurons in response to ischemia. Hamartin promotes survival by inhibiting mTORC1 and increasing autophagic flux in neurons.
Gesehen am 16.12.2021